2013
DOI: 10.1021/ma4002269
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Bisphenol A Polycarbonate and Its Tethered Nitrile Analogue

Abstract: The relative permittivity and dielectric strength have been determined for a bisphenol A polycarbonate (BPA-PC), in which a cyanoethyl group has been substituted for one of the geminal dimethyl groups. The new material (CN-PC) has a glass transition temperature that is 19 K higher than that for BPA-PC. In addition, the dielectric strength of CN-PC, 405 V/μm, is somewhat smaller than that for BPA-PC, 620 V/μm. The relative permittivity was determined from 10 to 10 5 Hz over a wide temperature range and at press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
65
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 25 publications
(63 reference statements)
0
65
0
5
Order By: Relevance
“…22,23 The idea is to utilize the free volume in high T g polymers to allow relatively free rotation of individual dipoles (i.e., sub-T g transitions 24 ) in order to enhance the dielectric constant while keeping dielectric loss low. 28 Stimulated by the above promising work, we here focus on high performance polyimides (PIs), which are attractive materials for use in highly aggressive environments because of their high T g , mechanical toughness, and resistance to solvents, radiation, heat and oxidation. 25,26 For example, poly(4-vinylbenzylcyanide) was reported to exhibit a dielectric constant as high as 7.0 at 100 kHz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 The idea is to utilize the free volume in high T g polymers to allow relatively free rotation of individual dipoles (i.e., sub-T g transitions 24 ) in order to enhance the dielectric constant while keeping dielectric loss low. 28 Stimulated by the above promising work, we here focus on high performance polyimides (PIs), which are attractive materials for use in highly aggressive environments because of their high T g , mechanical toughness, and resistance to solvents, radiation, heat and oxidation. 25,26 For example, poly(4-vinylbenzylcyanide) was reported to exhibit a dielectric constant as high as 7.0 at 100 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the rigid structure of the PIs, which does not allow dipoles to turn. Bendler et al 28 reported a study attaching cyanomethylene groups to bisphenol A polycarbonate (PC), having a CH 2 group between the main chain and the nitrile group so that the dipole could rotate more freely in the side group. Also, from Fig.…”
mentioning
confidence: 99%
“…Meanwhile,t he relatively low melting temperature (T m )o fa round 125 8 8Cp revents high-temperature operation. Thesecond example is adipolar glass polymer (note that the magnetic counterpart is as pin glass [11] ), where isolated molecular dipoles exhibit weak dipole-dipole interactions owing to the limited amount of free volume in glassy polymers.M ost dipolar glass polymers utilize highly polar groups such as nitrile [12] (dipole moment of 3.9 D) and sulfone [13] (4.5 D) groups.Relatively high dielectric constants in the range of 4-15 have been demonstrated for these dipolar glasses. [12][13] However, their glass transition temperatures (T g ) are relatively low and cannot meet the requirement of 150 8 8C ambient temperature for operation.…”
mentioning
confidence: 99%
“…Aromatic polycarbonates, as exemplified by bisphenol A‐based polycarbonates, are one of widely‐used polymers in various industrial applications because of their well transparency, high thermal stability, and mechanical properties . While, aliphatic polycarbonates feature biocompatibility and degradability, which inspires many scientists to explore the application to carriers of drugs and genes .…”
Section: Introductionmentioning
confidence: 99%